Microstructure characterization and thermal performance of reticulated SiC skeleton reinforced silica aerogel composites. (15th November 2019) - Ye, Xinli; Chen, Zhaofeng; Ai, Sufen; Hou, Bin; Zhang, Junxiong; Zhou, Qianbo; Wang, Fei; Liu, Hezhou; Cui, Sheng
Abstract: The silica aerogel composite reinforced by reticulated SiC skeleton (SiC/CF-Aerogel) was manufactured successfully via the chemical vapor deposition of the SiC coating and sol-gel process of silica aerogel in this paper. The results indicated that the SiC coating was deposited on the carbon skeleton with the induction of silica aerogel in the pores. The mechanical properties were enhanced due to the 3-dimensional reinforcement, which possessed a higher compressive response compared with the pure silica aerogel. Besides, SiC/CF-Aerogel possesses fine adiabatic performance with a thermal conductivity of 0.161 W m −1 K −1 at 700 °C. A physical heat model was proposed to illustrate the heat transfer to better understand the excellent thermal properties. It had a big practical potential for future applications.